Controlled Evaluation of the New BacT/Alert Virtuo Blood Culture System for Detection and Time to Detection of Bacteria and Yeasts - Altun, Osman (J Clin Microbiol, 2016)
We compared the newly approved BacT/Alert Virtuo blood culture system to the BacT/Alert 3D system using 115 clinical bacterial and fungal isolates in 784 simulated blood culture bottles. The time to detection was reduced by roughly 20% in the Virtuo system (P < 0.0001) while the detection rate did not differ.